Implementasi Metode Eklektik Pada Pembelajaran Bahasa Arab di Program Studi Non-Bahasa Arab Unira Malang - Sabila, Anis Nurma; Fitriani, Laily (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
The close relationship between Islamic studies and Arabic has caused many educational institutions including Islamic universities to design Arabic language learning in their curriculum, not only focusing on special Arabic study programs but also expanding to the curriculum of non-Arabic study programs such as Pendidikan Agama Islam (PAI). This is done to equip students with language skills to understand and interpret Islamic teachings. This research aims to describe 1) the objectives of learning Arabic at Raden Rahmat Islamic University, Malang; 2) the implementation of eclectic methods in learning Arabic at Raden Rahmat University, Malang. This research is field research with descriptive qualitative methods. Data was collected through observation, interviews, and documentation techniques and then used the Miles and Huberman model including data reduction, data presentation, and conclusion as data analysis techniques. The research results show that 1) the aim of teaching Arabic in the Pendidikan Agama Islam (PAI) study program is so that students can master Arabic language skills well to accompany their learning process in studying sources of Islamic knowledge such as the Al-Qur'an, hadith, and kitab turats despite such enormous challenges; and 2) implementation of eclectic methods in learning Arabic in the Raden Rahmat Islamic University at PAI study program, namely by combining the advantages of direct methods, nahwu grammar, translation, and audio-lingual so that teachers can create more meaningful and efficient learning to meet the stated course achievements has been formulated by the study program.